IS IT SAFE TO WITHDRAW COMBINED ANTIHYPERTENSIVE TREATMENT BEFORE NON-CARDIAC SURGERY IN THE VERY ELDERLY?. (June 2018) - Koutsaki, M.; Kallistratos, M.; Soulioti, E.; Poulimenos, L.; Thomopoulos, C.; Mela, A.; Batistaki, C.; Chatziagelaki, E.; Achimastos, A.; Koutsaki, S.; Khashlok, L.; Manolis, A.J.
Abstract : Objective: Elevated systolic blood pressure (SBP)during pre-operative evaluation is the main cause to postpone non-cardiac surgery. We hypothesized that white-coat phenomenon might be exaggerated in pre-operative visits. Design and method: During their perioperative visit, we prospectively enrolled 22 very elderly hypertensive patients (aged 78 ± 4) under chronic treatment with at least two antihypertensive agents. The day of the surgery this treatment was not administered except b-blockers according to guidelines. On-treatment office SBP, andBP immediately before and after surgery were recorded, while all the participants underwent ambulatory SBP measurement ranging from at least four hourspreoperatively, intraoperatively, to 4 hours postoperatively. A paired samples t-statistic was used for all comparisons after having checked for linearity and outliers. Results: Pre-operative on-treatment office SBP (142.2 ± 18mmHg) was significantly higher compared to inpatient SBP just before surgery (132.9 ± 19mmHg, P = 0.037); ambulatory SBP 4h-before surgery (130 ± 17mmHg, P = 0.004); ambulatory SBP during surgery (125.6 ± 17mmHg, P < 0.001); ambulatory SBP 4h-after surgery (126.6 ± 25mmHg, P = 0.022), and mean ambulatory SBP (129.9 ± 17mmHg, P = 0.004 In 17 patients (77.2%) pre-operative SBP was higher than 140/90mmHg (158.3 ± 16mmHg) despite ongoing treatment, and the difference with SBP before operation was also significant (142.3 + 17mmHg, P = 0.005). Conclusions: Office SBP during the usual pre-operative evaluation was significantly higher compared to SBP before, during and after surgery. A 24-hour withdrawal of any combined treatment was safe and was accompanied by significant SBP decrease, and this finding may stimulate randomized research in the field.